ESPIRITUALIDADE E EDUCAÇÃO PARA A LIBERDADE: o opressor hospedado no oprimido de Paulo Freire e a teoria do desejo mimético de René Girard - Soares, Adriana (2008)
This study discusses the relationship between spirituality and education for freedom from the anthropological perspective of human mimetic desire as key to the understanding of human relations, and spirituality as a fundamental dimension in the engagement in the battle for transformation of society. Through literature search, it is the analysis of the problem identified by Paulo Freire, that the oppressive "hosted" the oppressed represents an obstacle to the liberation, from the perspective of the theory of mimetic desire of René Girard. Works with the hypothesis that this essential element in anthropological thinking of Paulo Freire, forgotten as his pedagogical proposal assumed a character purely on conscience, refers to the dimension of spirituality. Because the distance between utopia of the liberation and the reality, establishes itself the scene of a crisis that falls not only on formal educators, but also on many of those who, at some point in their lives, whether in the battle for the engagement in social transformation. Since the method is well known, and it is acquire consciousness, the fact that the dreamed transformation has not occurred leads the conclusion that something failed in the process.(AU)